Poverty as a risk factor of mental health problems - Pūras, Dainius; Povilaitis, Robertas; Stanislavovienė, Jelena (Psichologija, 2003)
Health care specialists all over the world are entirely preoccupied with the growing distance between people’s health and their socio-economic level. In 1997 established International Poverty and Health Organization suggests to struggle against the problem by various means and one of them encompasses the possibility to include information how socio-economical differences affect people’s health into health care specialists training curricula. In many other countries respective studies are being carried out or are already done. Goal of the work: to detect the link between poverty and mental health problems. Methodology: The survey was done using the questionnaire created especially for this study and it was composed of 3 parts: demographic data, indicators of socio-economical status, mental health data. 1231 person were randomly selected and interviewed. Results: Correlation between incomes and mental health problems is established as follow: the strongest positive correlation (rs= 0,321) is between incomes and moods and the strongest negative correlation (rs = -0,368) is between incomes and how often people is in the state of sad and blue. It is established that there is a statistically reliable difference between answers to the questions about state of mental health of people who are in all poverty risk groups and who are not. It is also established that those who can not satisfy their minimal needs more often mark answers showing worse state of mental health.